Mobility, precarity and productivity: The uncertain expansion and migration of science in Portugal - Cairns, D. (Portuguese Journal of Social Science, 2022)
This article explores various aspects of the migration of science, including the circulation of scientific knowledge and the productivity of individual scientists. The first part of the article examines concepts that have helped define scientific employment, emphasizing the idea that a scientist’s work should align with an episteme. The second part scrutinizes this situation in Portugal, shedding light on two specific developments: the recent expansion of the scientific workforce and the outputs emanating from national research institutions. This includes a brief statistical overview of the levels of expansion in financial terms and an exploration of the success of scientific publishing using data derived from the Organization for Economic Cooperation and Development (OECD) and national statistics agencies. Data reveal that while the number of works produced has increased at a time during which greater numbers of scientists were being contracted, especially the decade preceding the COVID-19 pandemic, the impact of their work may have declined due to a lack of peer recognition, illustrated by a sharp decline in the number of citations received. This suggests that greater investment in science, specifically in recruiting fixed-term contract researchers, has not necessarily translated into measurable success. It also highlights the additional challenges posed by change in how scientific knowledge and scientists migrate.